THE ASSOCIATION OF ISLAMIC BASED CARING MODEL AND COMMITMENT TO ORGANIZATION IN STAFF NURSES - Yuda Ayu Timorita; Tri Hartiti; Bambang Edi Warsito; Suhartini Ismail (Belitung Nursing Journal, 2017)
Background: Strong organizational commitment is needed by hospitals to attract and retain nursing staffs in order to consistently deliver good quality of nursing services. The decrease in organizational commitment among nurses can cause many losses to the organization, including increased organizational spending, breakdown in patient care, and cause performance trends that appear not for the benefit of the organization or unit, but more for personal self-interest. Objective: To analyze the relationship of the application of Islamic Based Caring (IBC) model with organizational commitment among nurses. Methods: This was a correlation analytic research with cross sectional design. There were 108 nurses selected using a proportionate stratified random sampling. Islamic Based Caring was measured using a questionnaire developed based on the theory of Suhartini Ismail (2016), and organizational commitment was measured using a questionnaire developed based on the concept of Caldwell, O’Reilly & Chatmann (1990) and Mowday, Porter dan Steers (1982) in Asmaningrum (2009). Logistic regression and forward stepwise (conditional) method were used for data analysis. Results: There was a statistically significant correlation of a healing presence (p=0.000), caring relationship (p=0.010), caring environment (p=0.045) and belief in God (p=0.000). Belief in God (Allah SWT) has the highest correlation (OR=6.660) with organizational commitment among nurses. Conclusion: There is a positive and significant relationship between the implementation of Islamic Based Caring with the organization's commitment among nurses.